Identifikasi Ciri-Ciri Penyebab Perilaku Agresif Verbal dan Perilaku Agresif Non Verbal Pada SMP Negeri 13 Palangka Raya: Identification Of The Characteristics Of Verbal Agressive Behavior And Verbal Agressive Behavior In Palangka Raya 13 State SMP - Mohammad Andri Syarifullah; Dina Fariza Tryani Syarif (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to identify the characteristics of aggressive verbal behaviour and aggressive non-verbal behaviour. The type of research used is a quantitative descriptive approach. With a sample of 83 students. Data analysis using the percentage formula using SPSS software version 20. The results of the study show that: (1) the factors causing aggressive verbal behaviour of students in Palangka Raya Public Middle 13 are categorised as very dominant (84%) in the indicator denies. (2) The causes of non-verbal (physical) aggressive behaviour of students in Palangka Raya 13 Junior High School are categorised as very dominant. Namely, there are two indicators: indicators like to steal (90%), and signs wish to damage other people's property (86%)